Metal ion implantation into transparent dielectric slab: an effective route to high-stability localized surface plasmon resonance sensors. (29th October 2021) - Wang, Jun; Wang, Gang; Liu, Changlong; Wang, Yimo; Qian, Hui
Abstract: Ag/SiO2 and Au/SiO2 samples were prepared by separately implanting 30 keV Ag and Au ions into 0.5-mm-thick SiO2 slabs at a fluence of 6 × 10 16 ion·cm −2, and their optical and structural properties were studied in detail by using a fiber spectrometer and a transmission electron microscope, respectively. Our results showed that the two samples featured by their respective nanocomposite surface layers were asymmetrical in structure, and hence, their characteristic signals in the reflectance spectra excited by the lights incident from the rear surfaces were able to exhibit corresponding blueshifts when the overlays on the implanted surfaces were increased in refractive index with respect to air. Our results also showed that each of characteristic signals was strongly dependent on the localized surface plasmon resonance (LSPR) behavior of the involved Ag or Au nanoparticles (NPs), and it could not appear at a wavelength position smaller than or equal to that of the LSPR absorption peak since the involved Ag or Au NPs were quite small in size. These results meant that the two samples could be regarded as the LSPR sensors with a negative refractive index sensitivity (RIS), although their sensing abilities would lose when the overlays were very large in refractive index. Especially, the two samples were demonstrated to be relatively high in stability because the involved Ag and Au NPs were closely hugged and chemically protected by the matrices of SiO2, and consequently, they could have a chance to become prospective sensing devices in some special fields as long as their RISs and linearities could be improved in the future. The above findings substantially confirmed that the metal ion implantation into transparent dielectric slab was an effective route to the high-stability LSPR sensors.